2004
DOI: 10.1093/alcalc/agh042
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Perceptions of Community Responses and Attitudes to Service Provision: Results From a Survey of Indian, Chinese and Pakistani Young People in Greater Glasgow, Scotland, Uk

Abstract: Alcohol consumption in the target populations may be increasing and service provision could benefit by including specialist services for black and minority ethnic groups, in addition to mainstream services that need to be culturally sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
4
15
1
Order By: Relevance
“…In accordance with previous research, a diverse range of factors including individual personality and beliefs, peer behaviour, ethnicity, and religion influence whether masculinity is associated with excessive alcohol consumption (Best et al, 2001;Caspi et al, 1997;Heim et al, 2004;Johnston & White, 2003;Kuntsche et al, 2004;Wardle & Steptoe, 2003). This study revealed that within an socioeconomically-and ethnically-diverse sample of men aged 18-21 living in London there was a range of orientations toward hegemonic masculinity and alcohol consumption.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with previous research, a diverse range of factors including individual personality and beliefs, peer behaviour, ethnicity, and religion influence whether masculinity is associated with excessive alcohol consumption (Best et al, 2001;Caspi et al, 1997;Heim et al, 2004;Johnston & White, 2003;Kuntsche et al, 2004;Wardle & Steptoe, 2003). This study revealed that within an socioeconomically-and ethnically-diverse sample of men aged 18-21 living in London there was a range of orientations toward hegemonic masculinity and alcohol consumption.…”
Section: Discussionsupporting
confidence: 89%
“…For example, white British teenagers are more likely than their black and Asian peers to have ever drunk alcohol, and use alcohol regularly (Best, Rawaf, Rowley, Floyd, Manning & Strang, 2001;Denscombe, 1995;Karlsen, Rogers & McCarthy, 1998). Other UK research reveals that youth drinking varies as a function of ethnicity and religion (Heim et al, 2004): Pakistani-British youth are less likely to drink than IndianBritish or Chinese-British youth. Moreover, Muslim youth are less likely to drink than followers of other religions.…”
Section: Contexts Of Drinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an indicative (and non-exhaustive) list includes; studies of consumption, identity, lifestyle and forms of sociability that have considered gender differences and drinking patterns (Ettore, 1997;Harnett, Thom, Herring, & Kelly, 2000;Hunt & Satterlee, 1981;Plant, 1997;Robbins & Martin, 1993;Waterson, 2000), gender, age, sexuality (Bloomfield, 1993;Gough & Edwards, 1998) and the relationship between class and temperance (Jones, 1987). Studies have also looked at masculinity, femininity and ethnicity (Cochrane & Bal, 1990;Heim et al, 2004;McKeigue & Karmi, 1993;Shaikh & Nax, 2000), women who drink and expose themselves or fight (Day et al, 2004;Hugh-Jones, Gough, & Littlewood, 2005), men and violence (Benson & Archer, 2002), drinking amongst various black and minority ethnic groups (Share, 2003;Stivers, 2000), rural identities and drinking in the USA (Rooney & Butt, 1985) and alcohol culture in the Scottish Hebrides from the sixteenth to the twentieth century (Dean, 1995). Research has also focused on Irish drinking cultures and the proliferation of Irish theme pubs (McGovern, 2002), alcohol-related tourism in the Tyrol during the eighteenth century (Haid, 2003), adolescent drinking and family life in Scotland (Shucksmith, Glendinning, & Hendry, 1997), pub life in eighteenth-century Switzerland (Guggenbuhl, 2003), Czech men's drinking and the political climate from 1983-93 (Kubicka, Csemy, Duplinsky, & Kozeny, 1998), drinking amongst young people in seventeen-century Holland (Roberts, 2004), drinking and family relations in early modern Germany (Tlusty, 2004), drinking and masculinity in rural New Zealand (Campbell, 2000) and drinking and constructions of Britishness (Clarke, 1998).…”
Section: Alcohol Studies and Geographymentioning
confidence: 99%
“…A community survey in Glasgow [19] suggested that alcohol consumption may be increasing among Black and Minority Ethnic (BME) communities. A recent exploratory study of the Punjabi Sikh community in Birmingham points to anecdotal and practice-based evidence indicating that increasing numbers of Sikh men are presenting with alcohol-related liver disease resulting in hospital admissions [20].…”
Section: Alcohol Use and Misuse In Punjabi Sikh Communitiesmentioning
confidence: 99%